DO HEAVY METALS AFFECT ON DEHYDRATION RATE OF BRASSICA NAPUS, TRITICUM SPP., ZEA MAYS AND HORDEUM VULGARE? (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Dependence of dehydration rate of Brassica napus, Triticum spp., Zea mays and Hordeum vulgare from heavy metal concentrations in plants after its growth in contaminated media has been studied in the laboratory and results are summarized in this paper. We found water loss reduction in all plant species germinated in sewage sludge (somewhere soil) after 18 day in comparison with control samples, presented by garden compost. Moreover, water loss was reduced significantly in root part of the plants. At the same time water loss was increased in Brassica napus, Triticum spp. and Hordeum vulgare germinated in sewage sludge after 30 day in comparison with control samples that could have been caused by metals interactions with plants’ metabolic processes within the cells.